Coexistence of resistance to thyroid hormone and papillary thyroid carcinoma. (1st May 2016) - Igata, Motoyuki; Tsuruzoe, Kaku; Kawashima, Junji; Kukidome, Daisuke; Kondo, Tatsuya; Motoshima, Hiroyuki; Shimoda, Seiya; Furukawa, Noboru; Nishikawa, Takeshi; Miyamura, Nobuhiro; Araki, Eiichi
Summary: Resistance to thyroid hormone (RTH) is a syndrome of reduced tissue responsiveness to thyroid hormones. RTH is majorly caused by mutations in the thyroid hormone receptor beta ( THRB ) gene. Recent studies indicated a close association of THRB mutations with human cancers, but the role of THRB mutation in carcinogenesis is still unclear. Here, we report a rare case of RTH with a papillary thyroid carcinoma (PTC). A 26-year-old woman was referred to our hospital due to a thyroid tumor and hormonal abnormality. She had elevated serum thyroid hormones and non-suppressed TSH levels. Genetic analysis of THRB identified a missense mutation, P452L, leading to a diagnosis of RTH. Ultrasound-guided fine-needle aspiration biopsy of the tumor and lymph nodes enabled the cytological diagnosis of PTC with lymph node metastases. Total thyroidectomy and neck lymph nodes dissection were performed. Following surgery, thyroxine replacement (≥500 μg) was necessary to avoid the symptoms of hypothyroidism and to maintain her TSH levels within the same range as before the operation. During the follow-up, basal thyroglobulin (Tg) levels were around 6 ng/ml and TSH-stimulated Tg levels were between 12 and 20 ng/ml. Up to present, the patient has had no recurrence of PTC. This indicates that these Tg values are consistent with a biochemical incomplete response or an indeterminate response. There is no consensus regarding the management of thyroid carcinoma in patients with RTH, but aggressive treatments such as total thyroidectomy followed by radioiodine (RAI) and TSH suppression therapy are recommended. Learning points: There are only a few cases reporting the coexistence of RTH and thyroid carcinoma. Moreover, our case would be the first case presenting one with lymph node metastases. Recent studies indicated a close association of THRB mutations with human cancers, but the role of THRB mutation in carcinogenesis is still unclear. When total thyroidectomy is performed in patients with RTH, a large amount of thyroxine is needed to maintain their thyroid function. There is no consensus regarding the management of thyroid carcinoma in patient with RTH, but effective treatments such as total thyroidectomy followed by RAI and TSH suppression therapy are recommended.